Persepsi Guru PAI Terhadap Deep Learning : Analisis Hermeneutika dalam Konteks Pendidikan Islam - Hanifah Haliha Hanifah Haliha; Arum Puspita; Khamim Fauzi; Dhika Bintang; Sari Nuralita (Advances In Education Journal, 2025)
This research aims to deeply describe and analyze Islamic Religious Education (PAI) teachers' perceptions of the concept of deep learning in PAI teaching practices. Using a qualitative-hermeneutic phenomenological approach, this study attempts to interpret the meaning of deep learning based on teachers' reflective experiences, linking it to the philosophy of integrative Islamic education. Data was collected thru semi-structured in-depth interviews, observations, and document analysis (syllabi, lesson plans, teacher reflections) from selected PAI teachers in Bekasi and East Jakarta. The results will identify the conceptual implications of this deep learning interpretation for the development of a more reflective and meaningful (meaningful learning) PAI learning paradigm. This research is expected to contribute to the renewal of Islamic Religious Education (PAI) pedagogy that is oriented toward deep understanding, self-improvement, and manners.